2019
DOI: 10.1088/1361-648x/ab1026
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of photo-induced multiple topological phases on square-octagon lattice

Abstract: In this study, a tight-binding model on square-octagon lattice with nearest-neighbour and nextnearest-neighbour hoppings is considered. The system is topologically trivial although it exhibits quadratic band-touching points in its band-structure. It is shown that the system drives towards topologically non-trivial phases as soon as it is exposed to monochromatic circularly polarized light. Multiple topological phases are found to emerge with the variation of amplitude of light. An effective time-independent Ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Remarkably, SAI term has no role in this system while magnetic field is assumed to break the TRS. Emergence of photo-induced multiple topological phases is reported before in a tight-binding model on squareoctagon lattice 13 . Topological phases in the presence of spin-orbit coupling and magnetic field are also investigated on this lattice [14][15][16] .…”
Section: Introductionsupporting
confidence: 51%
“…Remarkably, SAI term has no role in this system while magnetic field is assumed to break the TRS. Emergence of photo-induced multiple topological phases is reported before in a tight-binding model on squareoctagon lattice 13 . Topological phases in the presence of spin-orbit coupling and magnetic field are also investigated on this lattice [14][15][16] .…”
Section: Introductionsupporting
confidence: 51%
“…This difference attributes to the fact that AFM ground state breaks the full symmetry of the Heisenberg Hamiltonian, while the singlet ground states in this study do not. Emergence of multiple topological phases in irradiated tightbinding and FM Kitaev-Heisenberg models on this lattice is noted before 25,26 . The effect of DMI cannot be registered either in POT or BOT because of the fact that, n (S n × S n+1 ) z vanishes identically over a plaquette and bond, when S is expressed in terms of either plaquette or bond operators, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…The band structure for τ = 1 and Θ = 0 has been previously investigated [46,47] and a remarkable feature for the square-octagon lattice is that one of the dispersive bands is sandwiched in between two perfectly flat bands, while the other is isolated from the rest, at the top of the spectrum, as depicted in Fig. 2.…”
Section: Flat Bandsmentioning
confidence: 99%
“…They range from a quantum magnetic phase under the competition between temperature and on-site repulsive interaction [41], to topological insulating phases induced by spin-orbit coupling or non-Abelian gauge fields [42][43][44], and even high-temperature superconductivity with singlet s ± -wave paring symmetry [45]. Moreover, it has been shown that trivial and nontrivial flat bands can be tuned on the square octagon lattice by considering the addition of next-nearest neighbour hopping and an external magnetic flux [46,47].…”
Section: Introductionmentioning
confidence: 99%